ANALISA YURIDIS TERHADAP TINDAK PIDANA PENGALIHAN OBYEK JAMINAN FIDUSIA TANPA PERSETUJUAN PENERIMA FIDUSIA - Nanin Koeswidi Astuti (to-ra, 2017)
Guarantee is one important element in the provision of credit, one of which is the guarantee of materiality. One of the known material guarantees in positive law is fiduciary guarantees. In the practice of credit provision by Bank through fiduciary credit guarantee institution to Bank customer, there is a possibility that there will be legal problem because the fiduciary guarantee object will remain in the hands of the customer of the Bank (debtor). With the enactment of Law No. 42/1999 on fiduciary collateral (UUJF) with criminal provisions, the legal protection of creditors from the crime of transferring fiduciary assets to third parties is given by UUJF when the creditor (fiduciary receiver) obtains fiduciary guarantee certificate by way of register a fiduciary guarantee deed made with a real note at the fiduciary registration office. Kata Kunci: Tindak Pidana Jaminan Fidusia, Obyek Jaminan Fidusia, Fidusia